CTE 2013: 2nd Workshop on Cloud Technologies in Education - Serhiy O. Semerikov; Andrii M. Striuk; Illia O. Teplytskyi (Academy of Cognitive and Natural Sciences, 2014)
The International Workshop will take place on December, 20, 2013 in Ukraine. It was an excellent occasion for specialists of different fields, e.g. IT specialists for e-learning design, e-learning tutors, teachers and lecturers, technologists, psychologists, educational managers and researchers to make a jump into new paradigm of Science and Education in High Tech Age.